2015
DOI: 10.1364/ao.54.002141
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced insulator-to-metal transition and surface statistics of VO_2 monitored by elastic light scattering

Abstract: Measurements of ultrafast light scattering within a hemisphere are performed for statistical analysis of nonequilibrium processes in VO2 epitaxial film. A Gerchberg-Saxton error reduction algorithm is applied for accurate calculation of a surface autocorrelation function from light scattering data and for partial reconstruction of a power spectral density function. Upon ultrafast photoinduced phase transition of VO2, the elastic light scattering reveals anisotropic grain-size-dependent dynamics. It was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 55 publications
2
9
0
Order By: Relevance
“…26,55,56 This algorithm was also applied to restore absent PSD s (f) data at the periphery up to f ¼ 2.1 lm À1 and in the central area of the scattering indicatrix blocked by the sample holder [ Fig. 1(b)].…”
Section: Surface Morphology and Domain Formationmentioning
confidence: 99%
“…26,55,56 This algorithm was also applied to restore absent PSD s (f) data at the periphery up to f ¼ 2.1 lm À1 and in the central area of the scattering indicatrix blocked by the sample holder [ Fig. 1(b)].…”
Section: Surface Morphology and Domain Formationmentioning
confidence: 99%
“…However, these techniques only partially resolve lattice relaxation dynamics, and many features remain hidden. After rigorous analysis of experimental data, several works [16,28,29,56,58] reported the presence of at least two stages of phase transition. Here, applying UDC technique the two stages of SPT process can be clearly resolved on a femtosecond time scale as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies of transient surface statistics [55,56] have shown the absence of coexistence of different VO 2 phases during the ultrafast phase transition. While slight variation of characteristic transition time was observed versus grain size, the pathway of SPT was identified as a coherent process across all spatial frequencies of the surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,[12][13][14][15][16][17] Most optical applications of VO 2 require essentially non-scattering properties, and both films and nanoparticle composites have been subject to detailed studies recently. 13,15 Only a few prior investigations 9,[18][19][20][21][22][23][24][25] have considered light scattering, and we particularly note recent work by Jin et al 20,21 on diffuse transmittance through VO 2 -based functional fiber mats and by Moot et al 22 on composites of VO 2 and elastomers.…”
Section: Introductionmentioning
confidence: 85%